Effects of vitamin E and phosphatidylcholine on qualitative and quantitative parameters of rainbow trout (Oncorhynchus mykiss) milt - Ivo Zoccarato; Rodolfo Ballestrazzi; Laura Gasco; Simona Rainis (Italian Journal of Animal Science, 2010)
The aim of this work was to investigate the effects of vitamin E and phosphatidylcholine on rainbow trout (Oncorhynchus mykiss) milt. One hundred and twelve rainbow trout (RB) broodstock (2n, 1030± 20g body weight, male:female ratio = 50:50) were fed four isoproteic and isolipidic diets for 110 days. Diets were differing for the type of vitamin premix and phosphatidylcholine supplied: Control (vitamin premix without Vit. E, no phosphatidylcholine); Vit.E (a premix with Vit. E, no phosphatidylcholine); PhC, (vitamin premix without Vit. E, phosphatidylcholine 2.5%); Vit.E +PhC, (vitamin premix with Vit. E and phosphatidylcholine 2.5%). Sperm total volume, in sexually mature males (3+; 966±114g body weight), ranged between 18.57ml (Control) and 34.31ml (Vit. E). Sperm density varied between 1.76x109 Szoa/ml (Control) and 1.16x109 Szoa/ml (Vit. E+PhC), while relative density (related to male body weight) tended to increase with Vit. E (>50x109 Szoa/ml) and to reduce with Vit. E + PhC (<30x109 Szoa/ml). Percentage motility was >85% in all treatments, while motility duration was around 2.37min for Vit. E and Control reached only 0.97min. After overnight storage (+4°C, for 18 hours) motility decreased, 75-80% in gamete motility and 3.39- 56.7% in time motility. PhC dietary supplements significantly increased arachidonic acid contents of sperm with respect to Control (>120 vs 73μg/ g), while Vit. E caused a huge increase in C20:3 n-3 (10.25 vs 2.27ppm). DHA/EPA ratio was significantly lower in Control (>2; p<0.05), while n-3/n-6 ratio was significantly the highest for Vit. E (9.46 vs <7.3).